From Bach's Goldberg to Beethoven's Diabelli: Influence and Independence - Kanwischer, Alfred (Rowman & Littlefield Publishers, 2014)
In From Bach’s Goldberg to Beethoven’s Diabelli: Influence and Independence, music scholar and noted pianist Alfred Kanwischer takes readers on an extended exploration in which each of the thirty-three pieces making up Beethoven’s Diabelli Variations (Op. 120) is caringly examined and assessed for its ingredients, actions, personality, and influence on the whole. Counterpoint abounds, not only in the fugal variations, which are closely parsed, but throughout the Diabelli, revealing the noticeably baroque character of the technical compositional devices Beethoven employs. Throughout his study, Kanwischer integrates comparisons with Bach’s immortal Goldberg Variations. Both sets stand alone as among the greatest keyboard variations in the Western canon. During their creation, the composers were nearly the same age, at the zenith of their art, and in similarly felicitous frames of mind. Kanwischer underscores twenty essential similarities, from the use of melody and melodic outline and the comparability among variations in size, parallel design, ebullient outlook, increasing contrasts, daring virtuosic flights, Shakespearean blend of comic and tragic, and their respective cumulative rises to spiritual transcendence. From Bach’s Goldberg to Beethoven’s Diabelli takes readers on a lively and stimulating journey of discovery. It considers not only questions of influence but those of insight and understanding, offering a work useful as a reference and as a guide to performers, music instructors, and devotees. This work also includes seventy visually annotated interpretive musical examples as aids to understanding.